Gestión por procesos como fundamento para la mejora continua en la empresa Frutos y Verdura de mi País S.A.S. - Quintero Sánchez, Daniel Eduardo; Flores Saes, Angie Vanessa (Universidad Antonio Nariño, 2021)
The present study aims to propose a process approach in the company Frutos y Verdura de mi País S.A.S, which aims at the distribution of inputs and / or products to welfare and schools. The research project consists of 3 objectives that are essential to carry out this thesis.